2009
DOI: 10.1111/j.1439-0272.2009.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the semen quality of patients with uraemia and renal transplant recipients in comparison with a control group

Abstract: To examine the semen quality of patients with uraemia and renal transplant recipients, 40 patients with uraemia and 40 renal transplant recipients were included. According to their interval of post-transplantation, renal transplant recipients were subdivided into group A (22) < or =2 years and group B (18) >2 years. A total of 40 healthy men with normal fertility were included as the controls. Semen samples from all subjects were collected and analysed. The fertility index (FI) value was calculated. The FI val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…In this study, it was indicated that CsA treatment significantly decreased sperm concentration and motility, and increased abnormal sperm rate in comparison with the control group. These results are in agreement with previous studies at which was indicated that CsA caused spermatozoal damage (Seethalakshmi et al, 1987;Seethalakshmi et al, 1990a, b;Iwasaki et al, 1996;Misro et al, 1999;Xu et al, 2003;Turk et al, 2007Turk et al, , 2010. Especially, sperm motility is an important functional measurement to predict sperm fertilizing capacity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, it was indicated that CsA treatment significantly decreased sperm concentration and motility, and increased abnormal sperm rate in comparison with the control group. These results are in agreement with previous studies at which was indicated that CsA caused spermatozoal damage (Seethalakshmi et al, 1987;Seethalakshmi et al, 1990a, b;Iwasaki et al, 1996;Misro et al, 1999;Xu et al, 2003;Turk et al, 2007Turk et al, , 2010. Especially, sperm motility is an important functional measurement to predict sperm fertilizing capacity.…”
Section: Discussionsupporting
confidence: 83%
“…However, several side effects have been associated with CsA treatment, such as hypertension, nephrotoxicity and neurotoxicity (Tavares et al, 2003). The previous studies reported that CsA caused toxicities such as testicular (Sirinivas et al 1998;Masuda et al, 2003) and spermatozoal toxicity (Seethalakshmi et al, 1990a, b;Iwasaki et al,1996;Misro et al, 1999;Xu et al, 2003). All alterations in mitochondrial functions, covalent binding of CsA metabolites to proteins, elevated thromboxane synthesis, and lipid peroxidation have been implicated in the CsAmediated cell damage (Seethalakshmi et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Kosar et al The explanation of the decrease in mean ST levels in unhealthy men in sub/infertility studies are not well known, but it is hypothesized that it is due to the action of interleukin-6 (IL6) in testis to reduces transferrin secretion in Sertoli cells (15). All sperm cell parameters evaluated (Table 1) were significantly lower in the case group than in the control group (p = 0.000), corroborating partially the results of other authors (16,17) that did not found significant differences for all the elements of the SP (16,17). However there is a study that did not show a significant difference in ST levels between healthy subjects and those with seminal quality alterations (18).…”
Section: Discussionsupporting
confidence: 79%
“…Currently, the best way to treat sexual dysfunction among men on hemodialysis is kidney transplantation [5]. Because approximately 40% of men receiving a kidney transplant are less than 50 years of age, reproductive function following transplantation is a major concern [6]. Kidney transplantation was reported to improve sexual function and sex hormone profiles [3, 7, 8].…”
Section: Introductionmentioning
confidence: 99%